Achieving a Realistic Notion of Time in Discrete Event Simulation - Georg Gaderer; Anetta Nagy; Patrick Loschmidt; Thilo Sauter (International Journal of Distributed Sensor Networks)
Distributed sensor systems require clock synchronization between all sensor nodes to provide consistent view of the overall system. Owing the growing size of networks, the evaluation of the synchronization performance becomes difficult, if done by means of experiments. Simulation is another method to tackle this issue. Realistic simulation of synchronization schemes requires accurate modelling of oscillators which are the driving timers generating various events. One way to characterise oscillators is to utilize the Allan variance, which can be used to generate a phenomenological model based on power spectral density. Since discrete event simulation (DES) tools are widely used to model network protocols, models which combine accuracy and performance are needed. This paper presents a model that was optimised for use in DES. To verify that the simulation results sufficiently match measurements, an implementation in OMNeT++ was done. The results show that the behaviour of distributed sensor systems, resulting from imperfect timebases, can be accurately simulated.